2020
DOI: 10.3390/cells9051292
|View full text |Cite
|
Sign up to set email alerts
|

Application of Oxidative Stress to a Tissue-Engineered Vascular Aging Model Induces Endothelial Cell Senescence and Activation

Abstract: Clinical studies have established a connection between oxidative stress, aging, and atherogenesis. These factors contribute to senescence and inflammation in the endothelium and significant reductions in endothelium-dependent vasoreactivity in aged patients. Tissue-engineered blood vessels (TEBVs) recapitulate the structure and function of arteries and arterioles in vitro. We developed a TEBV model for vascular senescence and examined the relative influence of endothelial cell and smooth muscle cell senescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…One achievement worth mentioning in this study is the establishment of AOPP-mediated senescent cell and animal models. Previous studies usually established senescent endothelial cell model through hydrogen peroxide (H 2 O 2 ) or Ang II treatment in vitro (31,43,44), while in vivo vascular senescence model was more commonly established by senescence accelerated mouse/prone (SAMP) model or transgenic mouse model, such as POLG-KO mouse (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…One achievement worth mentioning in this study is the establishment of AOPP-mediated senescent cell and animal models. Previous studies usually established senescent endothelial cell model through hydrogen peroxide (H 2 O 2 ) or Ang II treatment in vitro (31,43,44), while in vivo vascular senescence model was more commonly established by senescence accelerated mouse/prone (SAMP) model or transgenic mouse model, such as POLG-KO mouse (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from PCSK9, the same group also explored the effect of oxidative stress on inflammation and senescence on vascular cells using a 2-layered TEBV composed of endothelium and fibroblast layers. The data generated from the model suggested that oxidative stress promoted atherosclerosis by increasing vascular cell inflammation (165)(166)(167). Likely, Chen et al developed a 2layered EC-SMC TEBV.…”
Section: In Vitro 3d Vessel Based Systems Tissue-engineered Blood Vessels (Tebvs)mentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ), a major product of human metabolism, is an important indicator for monitoring and maintaining physiological balance of biological tissues in vivo. Unbalanced H 2 O 2 in the body leads to serious diseases, such as neurodegenerative Alzheimer's, [1] aging, [2] atherogenesis, [3] infarction, [4] cardiovascular diseases [5] and cancer [6] . Because of its great oxidizing capacity, H 2 O 2 is also extensively employed for sterilization and oxidative bleaching in the industrial, medicinal, and environmental protection fields.…”
Section: Introductionmentioning
confidence: 99%